Public theology and the translation imperative: A Ricoeurian perspective - Dreyer, J. S. (HTS teologiese studies, 2011)
The aim of this article is to contribute to the academic discussion on the inter-linguistic translation of the Christian message in the public sphere. There seems to be consensus amongst academic public theologians and social philosophers such as Habermas about the importance of translating religious language in the public sphere. Views differ, however, on the manner of translation. Five key aspects of Ricoeur’s paradigm of translation are discussed and offered as a framework for the academic discussion in public theology on the translation of the Christian message in the public sphere. It is argued that notions such as the tension between faithfulness and betrayal, the illusion of the perfect translation, striving for equivalence of meaning, the importance of the desire to translate, the work of translation and linguistic hospitality offer insight in the complexity of the translation task as well as its ethical nature.